EMPOWERING VILLAGE COMMUNITIES OF SURVIVORS THROUGH MASS CIRCUMCISION SERVICES - Taufiq; Zulmiardi; Ratna; Yanita; Syukriah; Bakhtiar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
The 2025 flood disaster in Ujong Pacu Village, Lhokseumawe City, disrupted access to preventive health services for children, including circumcision, which has medical, social, and religious aspects. This community service research aims to improve the health of flood survivor children through a community-based mass circumcision program. The implementation method uses a community-based intervention approach that includes preparation, medical procedures, and post-procedure monitoring and evaluation. Data were collected through activity observations, participant documentation, and post-circumcision health evaluations. The results of the activity indicate that the mass circumcision program, implemented continuously from 2015 to 2026, served 260 children with a 100% success rate without serious complications. This program not only improves children's preventive health but also strengthens social solidarity and the role of universities in post-disaster social rehabilitation. These findings confirm that community-based health interventions are effective as a community empowerment strategy in disaster-affected areas.